PENERAPAN METODE PEMBELAJARAN PICTORIAL RIDDLE TERHADAP MOTIVASI BELAJAR IPA FISIKA SISWA KELAS VIII SMP BEER SEBA PEKANBARU - Saragih, Nursani; Islami, Nur; Nasir, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The aim of this research is to describe the learning motivation of physics science with implementation of Pictorial Riddle. This type of research is a quasi-experimental, with a one-shot case study design. Samples in this research is all student of VIII B classes with total of 25 students. The instrument of data in this research is a ARCS motivation questionnaire. Analysis of the data in this study was a descriptive analysis that was used to view the category maotivation on learning physics science with the of use keller motivation formula. The analysis data shows score of students motivation are 5,33 with good category. Therefore, it can be concluded that implementation of Pictorial Riddle Learn Method can be used as an alternative method in the learning process in the classroom VIII SMP Beer Seba Pekanbaru.Keywords: ARCS motivation, light reflection, pictorial riddle.